Preparing fruit and vegetables for winter use - Riddle, Genevieve L. (My University, 1908)
Introduction: If the agitation and alarm excited by “Food scandals,” with the details of which the newspapers have reeked lately, have no other permanent result, they have revived the custom of domestic preserving in thousands of households. Canning is hardly fifty years old. It made its way but slowly for a time.
Citation: Riddle, Genevieve L. Preparing fruit and vegetables for winter use. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Food; Canning; Preservation; Domestic Science; Graduating theses; Senior theses; Theses